1988
DOI: 10.1128/mcb.8.7.2705
|View full text |Cite
|
Sign up to set email alerts
|

Genes that modify expression of major urinary proteins in mice.

Abstract: A survey of major urinary proteins (MUPs) from eight BALB/c mouse substrains by isoelectric focusing identified a common pattern with about 10 protein bands in males. One substrain, BALB/cJPt, differed The major urinary proteins (MUPs) of the mouse are a group of 19,000-molecular-weight, structurally and antigenically related proteins with isoelectric points (pls) in the range of pH 4.2 to 4.7. MUPs are synthesized predominantly in the liver but also in salivary, mammary, and other secretary glands. The MUPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Variation in Mup protein levels is observed in different strains of mice (29). This difference is most pronounced in BALB/cJ mice, which express Mups at considerably lower levels than what is seen in other strains, including other BALB/c substrains (30). This reduced Mup expression in BALB/cJ mice was mapped to a locus on mouse chromosome 15 (30).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Variation in Mup protein levels is observed in different strains of mice (29). This difference is most pronounced in BALB/cJ mice, which express Mups at considerably lower levels than what is seen in other strains, including other BALB/c substrains (30). This reduced Mup expression in BALB/cJ mice was mapped to a locus on mouse chromosome 15 (30).…”
mentioning
confidence: 94%
“…This difference is most pronounced in BALB/cJ mice, which express Mups at considerably lower levels than what is seen in other strains, including other BALB/c substrains (30). This reduced Mup expression in BALB/cJ mice was mapped to a locus on mouse chromosome 15 (30). The dramatic reduction in urinary Mup levels in BALB/cJ mice led us to investigate whether this trait was due to the Zhx2 mutation.…”
mentioning
confidence: 95%
“…Structurally, MUPs have molecular weights of about 19 kD and acidic isoelectric points in the range of 4.2 to 4.7 (Duncan et al 1988). A 2.4 Å crystal structure for MUP‐I isolated from mouse urine (Böcskei et al 1992) confirmed that MUPs are members of the lipocalin family of protein structures characterized by a conserved β‐barrel structure consisting of eight β‐strands and an α‐helix (for review, see Flower 1996).…”
mentioning
confidence: 99%
“…19 kDa. They are encoded by a multigene family which is differentially expressed in a number of secretory tissues [1–3], and the synthesis of these proteins, found only in the urine of sexually mature male mice, is under multihormonal control [4,5]. Thus, not surprisingly, urine turns out to be one of the main sources of olfactory chemosignals for mice, controlling for example sexual attraction among conspecifics, mating and puberty acceleration [6–8].…”
mentioning
confidence: 99%